Impact of public service motivation on nurses' job satisfaction and performance at RSUD Bahteramas Kendari - Nurjannah, Nurjannah; Montundu, Yusuf; Yusuf, Hayat (PT. Riset Press International, 2024)
This study aims to explain the influence of Public Service Motivation (PSM) on job satisfaction and the performance of nurses at Bahteramas Regional General Hospital in Kendari. Using an explanatory research method with a population of 211 nurses distributed across various work units, this study analyzes data using Structural Equation Modeling (SEM) supported by Amos software. The results show that Public Service Motivation has a positive and significant impact on both nurse performance and job satisfaction. Nurses with high motivation to serve the public tend to perform better and feel more satisfied with their work. Furthermore, job satisfaction is identified as an important factor that strengthens the influence of motivation on nurse performance. Based on these findings, it is recommended that hospital management take strategic steps to enhance nurse motivation and job satisfaction through training, workshops, and reward programs. Further research is suggested to explore other variables that affect nurse performance to improve the quality of healthcare services.